Dynamic Moral Hazard and Risk-Shifting Incentives in a Leveraged Firm - Rivera, Alejandro (Journal of Financial and Quantitative Analysis, 2020)
I develop an analytically tractable model that integrates the risk-shifting problem between bondholders and shareholders with the moral-hazard problem between shareholders and the manager. An optimal contract binds shareholders and the manager, and this contract’s flexibility allows shareholders to relax the manager’s incentive constraint following a “good” profitability shock. Thus, the optimal contract amplifies the upside and thereby increases shareholder appetite for risk shifting. Whereas some empirical studies find a positive relation between risk shifting and leverage, others find a negative relation. This model predicts a non-monotonic relation between risk shifting and leverage and can reconcile these contradictory empirical findings.